SUSTAINABILITY AND INTERMEDIARY SIGNALS SHAPING IPO UNDERPRICING UNDER CRISIS CONDITIONS - Wayan Eka Heltyani; Luh Gede Sri Artini (Adisam Publisher, 2026)
IPO underpricing remains a persistent phenomenon in capital markets, particularly during crisis periods when valuation uncertainty and information asymmetry intensify. This study addresses how firms and financial intermediaries convey credible signals to investors under such conditions. The research examines the role of sustainability-oriented corporate signals and intermediary credibility in shaping IPO underpricing, while assessing how crisis conditions influence signal effectiveness. A quantitative research design is applied using secondary data from firms conducting initial public offerings on the Indonesia Stock Exchange between 2020 and 2024. The final sample comprises 95 IPOs selected through purposive sampling, and the empirical analysis employs multiple linear regression and moderated regression techniques. The results indicate that stronger sustainability signals are associated with lower IPO underpricing, suggesting their effectiveness in mitigating perceived valuation risk. In contrast, higher intermediary credibility is linked to greater underpricing, reflecting conservative pricing strategies adopted to secure investor demand during turbulent periods. Crisis conditions amplify both relationships, underscoring the context-dependent nature of signal interpretation. The study concludes that sustainability disclosure enhances pricing efficiency under uncertainty, while intermediary credibility exerts a nuanced influence on IPO pricing outcomes during crises.